A rapid stress calculation method for short flexspline harmonic drive. Issue 6 (8th July 2019) - Wang, Shuang; Jiang, Gedong; Mei, Xuesong; Zou, Chuang; Zhang, Xian; Zhang, Hao
Abstract : Purpose: Because of the compact structure, short flexspline (FS) harmonic drive (HD) is increasingly used. The stress calculation of FS is very important in design and optimization of HD system. This paper aims to study the stress calculation methods for short FS, based on mechanics analysis and finite element method (FEM). Design/methodology/approach: A rapid stress calculation method, based on mechanics analysis, is proposed for the short FS of HD. To verify the stress calculation precision of short FS, a complete finite element model of HD is established. The results of stress and deformation of short FS in different lengths are solved by FEM. Findings: Through the rapid calculation method, the analytical relationship between circumferential stress and length of cylinder was obtained. And the circumferential stress has proportional relation with the reciprocal of squared length. The FEM results verified that the rapid stress calculation method could obtain accurate results. Research limitations/implications: The rapid mechanics analysis method is practiced to evaluate the strength of FS at the design stage of HD. And the complete model of HD could contribute to improving the accuracy of FEM results. Originality/value: The rapid calculation method is developed based on mechanics analysis method of cylinder and equivalent additional bending moment model, through which the analytical relationship between circumferential stress and length of cylinder was obtained. The complete three-dimensional finite element model of HD takes the stiffness of bearing into consideration, which can be used in the numerical simulation in the future work to improve the accuracy.